O programa institucional de bolsa de iniciação à docência na formação continuada de professores supervisores de Física - Batista, Leila Santos Freitas (2016)
The Institutional Program for Scholarships for Initiation in Teaching (PIBID) was established by the Ministry of Education as an incentive to the practice of teaching, through the approximation between university and school, theory and practice, trainees and trainers, valuing especially the training of undergraduate students through actions and pedagogical practices in school environment. However, this study launched to look at the formation of the housemaster, considering that in addition to being a trainer in the process, is also a subject in professional development learning and build your career through in everyday experience. Therefore, this study aimed to understand how the PIBID linked to the Federal University of Uberlândia has influenced the continued training of supervisors physics teachers. The research is a case study and a qualitative approach was the methodological inspiration for such use of semi-structured interviews and document analysis. Data were analyzed using content analysis and represented in five categories: PIBID Shares; appreciation of initial training; influence in practice; emphasis on pedagogical knowledge; emphasis on experience in PIBID. Thus, it was noticed that the actions and activities through PIBID, have potential to influence the continuing education of supervising teachers, by bringing to the university context and knowledge of new teaching opportunities. Among the results , it was identified that there is an appreciation of pedagogical knowledge, by inserting theoretical studies supporting the practice of education and experience in PIBID has been identified as a space for the practical reflection teaching and exchange of experiences among the subjects, although, not prioritize continuing education.